The Influence of E-WOM, Brand Trust and Promotion on Purchase Decision of The Originote Products on Tiktokshop - Mardhiana, Tryesa; Hariasih, Misti; Yani, Muhammad (Journal of Economics Education and Entrepreneurship, 2025)
This study aims to analyze the influence of E-WOM, Brand Trust, and Promotion on the purchase decision of The Originote products through Tiktokshop. The study uses a quantitative approach with a population of users of The Originote products who shop at Tiktokshop. The sample was determined using a non-probability sampling method with a purposive sampling technique, referring to the Rao Purba formula, resulting in 96 respondents. However, this abstract does not clearly explain the purposive sampling criteria used, so further explanation is needed to improve the clarity of the methodology. Data were collected through a questionnaire with interval and Likert scale measurements, but the constructs or items measured, such as E-WOM dimensions, Brand Trust aspects, and types of Promotion, were not detailed, making it difficult to assess the reliability and validity of the measuring instrument. Data analysis used the SmartPLS 3.0 application, and the results of the study showed that E-WOM had a significant positive influence on the Purchase Decision of The Originote Products at Tiktokshop, e-WOM on the e-commerce platform increased the perception of product quality and influenced consumer purchase intentions.  Brand Trust also has a significant positive influence on The Originote Product Purchase Decision on Tiktokshop, brand trust increases customer loyalty and encourages repeat purchases. Promotion also has a significant positive influence on The Originote product purchase decision on Tiktokshop, promotion on e-commerce platforms can significantly increase consumer purchase intentions.